(untitled) (Journal of Experimental and Clinical Anatomy, 2002)
The study of the effect of pesticide residues on the small intestinal morphometry of rats was undertaken using thirty Albino (Wistar) rats, which were separated into three groups (A, B, and C). The first group (A) was the control group and was fed normal rat chow. The first test group (B) was fed with the experimental diet after seven weeks of storage with the pesticide while the second test group (C) was fed with the experimental diet after fourteen weeks of storage with the pesticide. The pesticide of choice for the study was the cooper storage grain powder mixed at the rate of 0.5kg per ton and the feeding period after the storage lasted fourteen weeks. The results revealed that small intestinal morphometry of animals in the test groups were affected when compared with the control. The mucosa and the villi were reduced in height. The surface amplification factor due to the jejunal villi was 7, 4 and 5 for groups A, B. and C. respectively of which the level of difference was significant between the control group (A) and the test groups (B and C) (p<0.05), and in-between the test groups (A and B) (p<0.05).